Differentiation of Human Pluripotent Stem Cells Into Definitive Endoderm Cells in Various Flexible Three-Dimensional Cell Culture Systems: Possibilities and Limitations - Bogacheva, Mariia S.; Harjumäki, Riina; Flander, Emilia; Taalas, Ara; Bystriakova, Margarita A.; Yliperttula, Marjo; Xiang, Xiaoqiang; Leung, Alan W.; Lou, Yan-Ru (Frontiers in Cell and Developmental Biology, 2021)
The generation of human stem cell-derived spheroids and organoids represents a major step in solving numerous medical, pharmacological, and biological challenges. Due to the advantages of three-dimensional (3D) cell culture systems and the diverse applications of human pluripotent stem cell (iPSC)-derived definitive endoderm (DE), we studied the influence of spheroid size and 3D cell culture systems on spheroid morphology and the effectiveness of DE differentiation as assessed by qPCR, flow cytometry, immunofluorescence, and computational modeling. Among the tested hydrogel-based 3D systems, we found that basement membrane extract hydrogel could not retain spheroid morphology due to dominant cell-matrix interactions. On the other hand, we found that nanofibrillar cellulose hydrogel could maintain spheroid morphology but impeded growth factor diffusion, thereby negatively affecting cell differentiation. In contrast, suspension culture provided sufficient mass transfer and was demonstrated by protein expression assays, morphological analyses, and mathematical modeling to be superior to the hydrogel-based systems. In addition, we found that spheroid size was reversely correlated with the effectiveness of DE formation. However, spheroids of insufficient sizes failed to retain 3D morphology during differentiation in all the studied culture conditions. We hereby demonstrate how the properties of a chosen biomaterial influence the differentiation process and the importance of spheroid size control for successful human iPSC differentiation. Our study provides critical parametric information for the generation of human DE-derived, tissue-specific organoids in future studies.